Evaluating complex interventions: What are appropriate methods? - Masset, Eduardo (CEDIL, 2022)
In the CEDIL Methods brief, ‘Evaluating complex interventions: What ar e appropriate methods?’ we identify four types of complex development interventions: long causal chain interventions, multicomponent interve ntions, portfolio interventions, and system-level interventions. These interventions are characterised by multiple activities, multiple outc omes, multiple components, a high level of interconnectedness, and non -linear outcomes.